Fuzzy-Aided P–PI Control for Start-Up Current Overshoot Mitigation in Solid-State Lithium Battery Chargers - Chih-Tsung Chang; Kai-Jun Pai (Applied Sciences, 2025)
A battery charger for solid-state lithium battery packs was developed and implemented. The power stage used a phase-shifted full-bridge converter integrated with a current-doubler rectifier and synchronous rectification. Dual voltage and current control loops were employed to enable constant-voltage and constant-current charging modes. To improve the lifespan of the output filter capacitor, the current-doubler rectifier was adopted to effectively reduce output current ripple. During the initial start-up phase, as the charger transitions from constant-voltage to constant-current output mode, the use of proportional–integral control in the voltage and current loop error amplifiers may cause current overshoot during the step-rising phase, primarily due to the integral action. Therefore, this study incorporated fuzzy control, proportional control, and proportional–integral control strategies into the current-loop error amplifier. This approach effectively reduced the current overshoot during the step-rising phase, preventing the charger from mistakenly triggering the overcurrent protection mode. The analysis and design considerations of the proposed circuit topology and control loop are presented. Experimental results agree with theoretical predictions, thereby confirming the validity of the proposed approach.